Environmental Concerns, Sustainable Consumption, and COVID-19 Fear in Online Consumers: A Research Exploration - WONG, Wong Ming; QU, Mingjing; NUNUALVUTTIWONG, Chanidapha; NGAMCHAROENMONGKHON, Kobkullaya (Theoretical and Practical Research in Economic Fields, 2023)
As a conceptual paper, this study examines the nuanced relationships between consumers’ environmental orientations (egoistic, altruistic, and biospheric) and their sustainable consumption patterns, particularly emphasizing the prevailing influence of COVID-19 fear. Utilizing a targeted survey approach, responses from online Taiwanese and Thai consumers are gathered and analyzed through a Structural Equation Model, incorporating diverse analytical avenues such as path, mediation, moderation, and multi-group analyses. The study aims to describe prosocial consumers by their distinct environmental concerns and subsequent sustainable consumption behaviors. Furthermore, the study sheds light on how the COVID-19 pandemic has modulated the dynamic between environmental considerations and tangible sustainable consumption actions. In a post-pandemic setting, the study contributes to academic discourse by highlighting the confluence of environmental consciousness and sustainable consumption. It also provides pragmatic implications for businesses, directing them towards eco-centric product offerings and cultivating a deeper ecological awareness among consumers, fostering sustainable purchase intention and behaviors.